2023
DOI: 10.3390/ijms24043917
|View full text |Cite
|
Sign up to set email alerts
|

BRM Complex in Arabidopsis Adopts ncBAF-like Composition and Requires BRD Subunits for Assembly and Stability

Abstract: ATP-dependent SWI/SNF chromatin remodelling complexes are conserved multi-subunit assemblies that control genome activity. Functions of SWI/SNF complexes in plant development and growth have been well established, but the architecture of particular assemblies is unclear. In this study, we elucidate the organization of Arabidopsis SWI/SNF complexes formed around a BRM catalytic subunit, and define the requirement of bromodomain-containing proteins BRD1/2/13 for the formation and stability of the entire complex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Specifically, BRD1 (At1g20670), BRD2 (At1g76380) and BRD13 (At5g55040) were co-purified with subunits of Arabidopsis SWI/SNF complexes [ 57 ]. Subsequent studies have demonstrated that BRD1, BRD2 and BRD13 are unique components of Arabidopsis SWI/SNF complexes, thereby introducing the presence of non-ATPase BRD-containing subunits in these complexes [ 58 , 59 , 60 ]; however, note that they do not contribute equally to their formation of BRM-containing SWI/SNF complexes [ 60 ]. Comparative analysis indicated that BRD1, BRD2 and BRD13 are highly similar and clustered into a single phylogenetic cluster.…”
Section: Bromodomain Proteins Of Chromatin-remodeling Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, BRD1 (At1g20670), BRD2 (At1g76380) and BRD13 (At5g55040) were co-purified with subunits of Arabidopsis SWI/SNF complexes [ 57 ]. Subsequent studies have demonstrated that BRD1, BRD2 and BRD13 are unique components of Arabidopsis SWI/SNF complexes, thereby introducing the presence of non-ATPase BRD-containing subunits in these complexes [ 58 , 59 , 60 ]; however, note that they do not contribute equally to their formation of BRM-containing SWI/SNF complexes [ 60 ]. Comparative analysis indicated that BRD1, BRD2 and BRD13 are highly similar and clustered into a single phylogenetic cluster.…”
Section: Bromodomain Proteins Of Chromatin-remodeling Complexesmentioning
confidence: 99%
“…brd1, brd2 and brd13 mutants display early flowering compared to wt plants, indicating that BRD1, BRD2 and BRD13 act as repressors of flowering. Since double mutants presented pronounced phenotypes, a functional redundancy of these BRD-proteins is thought to occur, even though the levels of redundancy differ between them [ 58 , 59 , 60 ]. In comparison to single and double mutants, brdx3 triple mutants exhibited a general reduction in size, along with the production of smaller, curled leaves, shorter roots, early flowering and reduced fertility [ 58 , 59 ], a phenotype similar to brm mutants [ 58 , 59 ].…”
Section: Bromodomain Proteins Of Chromatin-remodeling Complexesmentioning
confidence: 99%
“…Most of the SWI/SNF complex subunits have been revealed to play important roles in multiple processes of plant development, such as leaf, root, floral organ and seed development, flowering time control, shoot apical meristem maintenance, chlorophyll biosynthesis, and response to phytohormone ( Shang and He, 2022 ). The multi-copies of some subunits exhibit redundant functions like MINU1/2, BRD1/2/13, BRIP1/2, BDH1/2, and TPF1/2 ( Sang et al., 2012 ; Yu et al., 2020 ; Jaronczyk et al., 2021 ; Diego-Martin et al., 2022 ; Stachula et al., 2023 ). On the contrary, SWI3 proteins act non-redundantly to control different aspects of development ( Sarnowski et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%